Upaya Guru Pendidikan Agama Islam Dalam Mengimplementasikan Pendidikan Akhlak Bagi Generasi Z - Rukhuddin Maulana Fakhrur Rizal; Rosichin Mansur; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to: 1) Describe the moral picture of students in Mts Hasyim Asyari Kota Batu; 2) What are the factors that support and hinder the implementation of moral education in Mts Hasyim Asyari Kota Batu; 3) What is the effort of Islamic religious education teachers in implementing moral education for generation Z in the Mts Hasyim Asyari Kota batu. This research was carried out because it was sad to see the morals of the generation born where the technology was advanced because they had been affected by the negative effects of the development of the era. The results of this study indicate that: 1) Most children in the past in terms of behavior or behavior to the teacher is still fairly good. Because the teaching methods provided by teachers or old-age parents are more disciplined especially in terms of educating. Another case in the current generation of children, they seem like spoiled and complacent by the rapid development of the times. Where technology has developed rapidly and some parents sometimes give less attention to their children because they may be too busy at their respective jobs. From this lack of attention and control of parents to children, this usually causes the current generation to be less good. 2) Supporting factors in the implementation of moral education in Mts Hasyim Asyari Kota Batu, Mrs. Khamida explained that the success of an institution is not supported by one side only. This means that the success of an institution in supporting the implementation of moral education can be assessed not only from the success of a teacher in pursuing moral education alone, but also the success of parents as a more important role in forming student behavior in the family environment. In the formation of morals, more precisely done since as early as possible so that the application of moral education can run well and later the child can have akhlakul karimah as expected. 3) Even though the teacher has tried his best so that the implementation of moral education can run well, it would be better here that the role of parents as their child educators in the family sphere must also try to support so that the implementation of moral education for their children can run well and is expected a child can be a person of moral character as expected.